The energy spectra of electron microbursts and their source populations - E.J. Engel; J. Sample; A.T. Johnson; M. Shumko; W.L. Wetzel; D.M. Klumpar (Advances in Space Research, 2026)

SNAPSHOT USA 2024: Year 6 of the Coordinated National Camera Trap Survey of the United States - Brigit Rooney; Roland Kays; Michael V. Cove; Alex Jensen; Daniel J. Herrera; Camilla Price; Phuong‐Thao Nguyen‐Nu; Katrina Adamczyk; Peter D. Alexander; David Allen; Jesse M. Alston; Diego F. Alvarado‐Serrano; et al. (Global Ecology and Biogeography, 2026)
Motivation SNAPSHOT USA is an annual, multi‐contributor camera trap survey of mammals across the United States. The growing SNAPSHOT USA dataset is intended for tracking the spatial and temporal responses of mammal populations to changes in land use, land cover and climate. These data will be useful for exploring the drivers of spatial and temporal changes in relative abundance and distribution, as well as the impacts of species interactions on daily activity patterns. Main Types of Variables Contained SNAPSHOT USA 2024 contains 377,427 records of camera trap image sequence data and 3127 records of camera trap deployment metadata. Spatial Location and Grain Data were collected across the United States of America in 49 states, 12 ecoregions and many ecosystems. Time Period and Grain Data were collected between 1 August and 19 December in 2024. Major Taxa and Level of Measurement The dataset includes a wide range of taxa but is primarily focused on medium to large mammals. Software Format SNAPSHOT USA 2024 comprises two .csv files. The original data can be found within the SNAPSHOT USA 2024 project on the Wildlife Insights platform.

Evaluating the combined effects of climate and land use change on hydrological response in a mixed land use watershed - Hossein Ahmadi; Durelle Scott; David J. Sample; Siddharth Saksena (Journal of Environmental Management, 2026)

Impacts of climate change on storm event-based flow regime and channel stability of urban headwater streams - Sami Towsif Khan; David J. Sample; Theresa Wynn-Thompson; Jon Butcher (Journal of Environmental Management, 2025)

SNAPSHOT USA 2021: A third coordinated national camera trap survey of the U nited S tates - Hila Shamon; Roi Maor; Michael V. Cove; Roland Kays; Jessie Adley; Peter D. Alexander; David N. Allen; Maximilian L. Allen; Cara L. Appel; Evan Barr; Erika L. Barthelmess; Carolina Baruzzi; et al. (Ecology, 2024)
SNAPSHOT USA is a multicontributor, long‐term camera trap survey designed to survey mammals across the United States. Participants are recruited through community networks and directly through a website application ( https://www.snapshot-usa.org/ ). The growing Snapshot dataset is useful, for example, for tracking wildlife population responses to land use, land cover, and climate changes across spatial and temporal scales. Here we present the SNAPSHOT USA 2021 dataset, the third national camera trap survey across the US. Data were collected across 109 camera trap arrays and included 1711 camera sites. The total effort equaled 71,519 camera trap nights and resulted in 172,507 sequences of animal observations. Sampling effort varied among camera trap arrays, with a minimum of 126 camera trap nights, a maximum of 3355 nights, a median 546 nights, and a mean 656 ± 431 nights. This third dataset comprises 51 camera trap arrays that were surveyed during 2019, 2020, and 2021, along with 71 camera trap arrays that were surveyed in 2020 and 2021. All raw data and accompanying metadata are stored on Wildlife Insights ( https://www.wildlifeinsights.org/ ), and are publicly available upon acceptance of the data papers. SNAPSHOT USA aims to sample multiple ecoregions in the United States with adequate representation of each ecoregion according to its relative size. Currently, the relative density of camera trap arrays varies by an order of magnitude for the various ecoregions (0.22–5.9 arrays per 100,000 km 2 ), emphasizing the need to increase sampling effort by further recruiting and retaining contributors. There are no copyright restrictions on these data. We request that authors cite this paper when using these data, or a subset of these data, for publication. Any use of trade, firm, or product names is for descriptive purposes only and does not imply endorsement by the US Government.

Parameterization of nutrients and sediment build-up/wash-off processes for simulating stormwater quality from specific land uses - Mina Shahed Behrouz; David J. Sample; Odhiambo B. Kisila; Michael Harrison; Mohammad Nayeb Yazdi; Roja Kaveh Garna (Journal of Environmental Management, 2024)

Robustness of storm water management model parameter sets for dry and wet hydroclimatic conditions - Mina Shahed Behrouz; David J. Sample; Mohammad Nayeb Yazdi (Journal of Cleaner Production, 2023)

Selection rankings of woody species for white-tailed deer vary with browse intensity and landscape context within the Central Hardwood Forest Region - Richard D. Sample; Zackary J. Delisle; Jameson M. Pierce; Robert K. Swihart; Joe N. Caudell; Michael A. Jenkins (Forest Ecology and Management, 2023)

The effect of piping stream channels on dissolved oxygen concentration and ecological health - Mehdi Ketabchy; Elyce N. Buell; Mohammad Nayeb Yazdi; David J. Sample; Mina Shahed Behrouz (Environmental Monitoring and Assessment, 2023)

Sex differences in associations between birth characteristics and childhood cancers: a five-state registry-linkage study - Lindsay A. Williams; Jeannette Sample; Colleen C. McLaughlin; Beth A. Mueller; Eric J. Chow; Susan E. Carozza; Peggy Reynolds; Logan G. Spector (Cancer Causes & Control, 2021)

Response of non-point source pollution to landscape pattern: case study in mountain-rural region, China - Wuhua Li; Xiangju Cheng; Yu Zheng; Chengguang Lai; David J. Sample; Dantong Zhu; Zhaoli Wang (Environmental Science and Pollution Research, 2021)

Evaluating the Impact of Climate Change on Water Quality and Quantity in an Urban Watershed Using an Ensemble Approach - Nasrin Alamdari; David J. Sample; Andrew C. Ross; Zachary M. Easton (Estuaries and Coasts, 2020)

Assessing nitrogen and phosphorus removal potential of five plant species in floating treatment wetlands receiving simulated nursery runoff - Jonathan T. Spangler; David J. Sample; Laurie J. Fox; Joseph P. Albano; Sarah A. White (Environmental Science and Pollution Research, 2019)

Ecosystem service flows from a migratory species: Spatial subsidies of the northern pintail - Kenneth J. Bagstad; Darius J. Semmens; James E. Diffendorfer; Brady J. Mattsson; James Dubovsky; Wayne E. Thogmartin; Ruscena Wiederholt; John Loomis; Joanna A. Bieri; Christine Sample; Joshua Goldstein; Laura López-Hoffman (Ambio, 2019)

Long-term trends in seasonal plankton dynamics in Lake Mead (Nevada-Arizona, USA) and implications for climate change - John R. Beaver; Janet E. Kirsch; Claudia E. Tausz; Erin E. Samples; Thomas R. Renicker; Kyle C. Scotese; Heidi A. McMaster; Becky J. Blasius-Wert; Paul V. Zimba; Dale A. Casamatta (Hydrobiologia, 2018)

Evaluating the performance of a retrofitted stormwater wet pond for treatment of urban runoff - Daniel Schwartz; David J. Sample; Thomas J. Grizzard (Environmental Monitoring and Assessment, 2017)

Ecosystem services in managing residential landscapes: priorities, value dimensions, and cross-regional patterns - K. L. Larson; K. C. Nelson; S. R. Samples; S. J. Hall; N. Bettez; J. Cavender-Bares; P. M. Groffman; M. Grove; J. B. Heffernan; S. E. Hobbie; J. Learned; J. L. Morse; et al. (Urban Ecosystems, 2016)

Dietary toxicity of soluble and insoluble molybdenum to northern bobwhite quail (Colinus virginianus) - Jennifer M. Stafford; Charles E. Lambert; Justin A. Zyskowski; Cheryl L. Engfehr; Oscar J. Fletcher; Shanna L. Clark; Asheesh Tiwary; Cynthia M. Gulde; Bradley E. Sample (Ecotoxicology, 2016)

Frequency Analysis for Precipitation Events and Dry Durations of Virginia - Jia Liu; David J. Sample; Haibo Zhang (Environmental Modeling & Assessment, 2014)

Experimental infection of laboratory-bred bank voles (Myodes glareolus) with murid herpesvirus 4 - David J. Hughes; Anja Kipar; Gail Leeming; Jeffery T. Sample; James P. Stewart (Archives of Virology, 2012)

CTCF and Sp1 interact with the Murine gammaherpesvirus 68 internal repeat elements - Hannah C. Stevens; Kevin S-W Cham; David J. Hughes; Ren Sun; Jeffery T. Sample; Vivien J. Bubb; James P. Stewart; John P. Quinn (Virus Genes, 2012)

An ancient linked fluid migration system: cold-seep deposits and sandstone intrusions in the Panoche Hills, California, USA - Hilde Schwartz; James Sample; Kevin D. Weberling; Daniel Minisini; J. Casey Moore (Geo-Marine Letters, 2003)

Thermal-pH inactivation of herpes simplex virus: Interdependence of the medium composition and the pH on the rate of virus inactivation - G. Lancz; J. Sample (Archives of Virology, 1985)